The effect of lift thicknesses on thermal stresses in roller compacted concrete (RCC) gravity dam - Hagos, Birhane Gebreyohannes; Parvathi, I. Siva; Praveen, T.V. (Journal of Structural Engineering, 2024)
A two dimensional thermal stress analysis of a zoned roller compacted concrete gravity dam, viz., Gibe-III RCC gravity dam of 214m high non-overflow section is carried out for predicting non-uniform development of temperature in hydrating concrete with respect to time and space during its construction using finite element method. The influence of the thermal properties and the climatic conditions, and the placement schedule of RCC layers are considered in the analysis. The available laboratory heat of hydration data and the incremental construction process of mass-concrete structure are modeled to produce results that can be used in construction planning and casting schedule of RCC dams. The present study considers three lift layer thicknesses, i.e., 3m, 4m and 6m in the construction of Gibe-III RCC gravity dam, and temperature and thermal stress distribution corresponding to each lift thickness has been computed. The probability of crack occurrence due to the change in the temperature gradients in the core and surface of the dam is also calculated. The study demonstrates that detailed thermal stress analysis should be performed for large RCC gravity dam like Gibe-III in order to minimize and control the occurrences of thermal cracking.